2020
DOI: 10.1021/acsomega.0c00898
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Designed Sesamol Derivatives Proposed as Potent Antioxidants

Abstract: Oxidative stress has been recognized to play an important role in several diseases, such as Parkinson’s and Alzheimer’s disease, which justifies the beneficial effects of antioxidants in ameliorating the deleterious effects of these health disorders. Sesamol, in particular, has been investigated for the treatment of several conditions because of its antioxidant properties. This article reports a rational computational design of new sesamol derivatives. They were constructed by adding four functional groups (−O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 80 publications
2
49
0
Order By: Relevance
“…[66] Recent observations suggest that bromocriptine is a free-radical scavenger that scavenges hydroxyl and superoxide radicals in vitro and acts as an antioxidant that inhibits free-radical formation. [67] Based on these properties, it was reported that cytoprotective mechanism of bromocriptine against oxidative damage in H 2 O 2 -treated PC12 cells. Bromocriptine oxidative damage, and increased the expression and nuclear translocation of Nrf2.…”
Section: Antioxidant Compounds In Experimental Models Of Pdmentioning
confidence: 99%
“…[66] Recent observations suggest that bromocriptine is a free-radical scavenger that scavenges hydroxyl and superoxide radicals in vitro and acts as an antioxidant that inhibits free-radical formation. [67] Based on these properties, it was reported that cytoprotective mechanism of bromocriptine against oxidative damage in H 2 O 2 -treated PC12 cells. Bromocriptine oxidative damage, and increased the expression and nuclear translocation of Nrf2.…”
Section: Antioxidant Compounds In Experimental Models Of Pdmentioning
confidence: 99%
“…Among the newer approaches, the parameters fitting method ( 182 , 183 ) stands out not only due to its much simpler computation protocol but also the accuracy reported in the number of studies that have used it. 36 , 41 , 46 , 73 , 85 , 101 , 112 , 126 It employs a linear regression model to determine p K a values for hydroxyl, carboxylic, amino, and thiol groups in a water solvent. Mathematically, it is expressed by eq 9 where Δ G AntoxOH/Antox – * denotes the difference in Gibbs free energy between the antioxidant’s conjugated base and the corresponding acid, and m and C are empirical parameters available for 20 different functionals, each in one of four Pople’s basis sets.…”
Section: Preliminary Concernsmentioning
confidence: 99%
“…It is similar to DAM, but the axes changes, so the Y axis corresponds to ω, while the X axis refers to BDE. As a result, the species in the left-bottom region are more likely to work in both directions, making them particularly valuable as radical scavengers, such as new sesamol 112 or melatonin derivatives 101 , or modified p-coumaric acid analogs with neuroprotective activity. 46 In most cases, parent molecules, oxidants, or reference antioxidants, e.g.…”
Section: Electronic Structure Investigationsmentioning
confidence: 99%
“…The Grimmes's dispersion correction (GD3) [39] was added to this functional in order to strengthen the description of weak interactions. The reliability of the M05-2X functional in computing thermodynamic based AOA parameters has also been largely demonstrated [40][41][42]. Geometry optimization of all structures was followed by frequency calculations and no imaginary frequency has been obtained.…”
Section: Computational Proceduresmentioning
confidence: 99%